Theta rhythm and the encoding and retrieval of space and time - Hasselmo, Michael E. (2013)
Physiological data demonstrates theta frequency oscillations associated with memory function and spatial behavior. Modeling and data from animals provides a perspective on the functional role of theta rhythm, including correlations with behavioral performance and coding by timing of spikes relative to phase of oscillations. Data supports a theorized role of theta rhythm in setting the dynamics for encoding and retrieval within cortical circuits. Recent data also supports models showing how network and cellular theta rhythmicity allows neurons in the entorhinal cortex and hippocampus to code time and space as a possible substrate for encoding events in episodic memory. Here we discuss these models and relate them to current physiological and behavioral data.